Cardiovascular risk factors in an HIV infected rural population of Limpopo Province, South Africa - Mashinya, Felistats (University of Limpopo, 2016)
Refer to document
Thesis (Ph. D. (Medical Sciences)) -- University of Limpopo, 2016
Keywords: Cardiovascular risk factors; HIV/AIDS; Rural population; HIV (Viruses) -- South Africa; Cardiovascular system -- Diseases -- Risk factors; Clinical medicine